Surgical treatment of tertiary hyperparathyroidism: does one fit for all? - Casella, Claudio; Guarneri, Claudio; Campanile, Manuela; Adhoute, Xavier; Gelera, Pier Paolo; Morandi, Riccardo (Frontiers in Endocrinology, 2023)
Background: Tertiary hyperparathyroidism (3HPT) is defined as a condition of excessive autonomous excretion of intact parathyroid hormone (iPTH) with persistent hypercalcemia (>10.5 mg/dL) that lasts for more than 12 months after a successful kidney transplantation, in the context of a long course secondary hyperparathyroidism (2HPT). The chronic high levels of iPTH causes a worsening of graft function, accompanied by systemic symptoms of hypercalcemia. The only curative therapy is parathyroidectomy (PTX). It remains unclear whether total parathyroidectomy with autotransplant (TPTX-AT) or subtotal parathyroidectomy (SPTX) lead to better outcomes.The aim of this retrospective, single-institution cohort study is to evaluate the rate of persistent or recurrent disease and postoperative calcium/iPTH disturbances in patients treated with TPTX-AT or SPTX for 3HPT.Methods: Single centre retrospective analysis of 3HPT patients submitted to TPTX-AT or SPTX between 2007-2020 with at least 24 months follow up. Outcome parameters included persistence/recurrence of disease, incidence of transitory hypocalcemia and temporary/permanent hypoparatiroidism.Results: A cohort of 52 patients was analysed and divided in two groups: 38 (73%) were submitted to TPTX-AT, and 14 patients (27%) were submitted to SPTX. TPTX-AT population showed lower plasmatic calcium concentration over SPTX group during the entire follow up period (p<0.001). Eight cases (21%) of transitory hypocalcemia in TPTX-AT, none in SPTX group with p=0.065. Two cases (5%) of temporary hypoparathyroidism in TPTX-AT, none in SPTX group with p= 0.530. No cases of permanent hypoparathyroidism. No cases of persistent disease. No statistical difference was assessed for the recurrence of 3HPT between the TPTX-AT group and the SPTX group (N=1, 3% vs N=1, 7%) (p=0.470).No significative difference was registered between TPTX-AT and SPTX groups in terms of persistence/recurrence of disease, incidence of transitory hypocalcaemia and temporary/permanent hypoparatiroidism. Mean calcium levels iPTH values were statistically lower among TPTX-AT compared to SPTX while remaining always in the range of normality.